Investigasi Determinan Earning Management - Alfiana Alfiana; Irwan Moridu; Donny Dharmawan; Ninik Churniawati; Dwi Budi Srisulistiowati (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The purpose of the study was to examine the effect of profitability variables (ROA), and company size (SIZE) on earnings management. This study uses data obtained from the annual financial statements of Manufacturing Companies listed on the Indonesia Stock Exchange in 2015-2017. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2019-2013 totaling 197 companies. At the purposive sampling stage, the number of samples that are suitable for use is 18 Manufacturing Companies. The data analysis method is multiple linear regression. Hypothesis testing uses the t-test to partially test the variables, as well as the F-test. The results of the analysis show that partially profitability (ROA) affects earnings management. But company size (Size) has no effect on earnings management. Then the results of the regression analysis detected that simultaneously profitability (ROA) and company size (Size) showed an influence on earnings management (Earning Management) of 54.8%, the remaining 45.2% being influenced by other factors.